A tool to assess underlying factors to water provision among Guinean children - Nèmanan Richard Ninamou; Jérémie B. Dupuis; Noël‐Marie Zagré; Mamady Daffé; Sonia Blaney (Wiley, 2022)
Abstract In many countries, water is provided to children under 6 months of age (CU6M) in addition to breast milk (BM), hence increasing the risk of child mortality and morbidity. Factors related to this practice have not been thoroughly investigated either a tool to assess them. Based on the extended theory of planned behaviour (eTPB), we aim to develop and validate a questionnaire to assess psychosocial and environmental factors that may contribute/limit the water provision in addition to BM by mothers of CU6M in the Republic of Guinea. A three‐step process was used. Ten focus group discussions (FGDs) were held to identify salient beliefs related to each of the four constructs of the eTPB. Data from FGDs were used to develop a questionnaire composed of 88 items administered to 428 mothers. Exploratory factor analyses were conducted to identify latent factors for each construct. A shorter version of the questionnaire was administered to another sample of 300 mothers. Confirmatory factor analyses (CFAs) were performed. Hancock and Mueller's H reliability indices were computed on final models to assess the tool's validity and reliability. The final questionnaire included 57 items. For all four final models, most criteria for fit indices of CFA were generally met. Reliability coefficients were all equal to or above 0.90 for each construct. This research offers a tool that could be used to investigate determinants of water provision besides BM among mothers of CU6M. Further validation in other contexts is warranted.